Higher Education in Britain Oxford University is a model General (1852-1996) Historical study - Abdul Jabbar Ibrahim., Tamadhur (Journal of College of Education, 2019)
The study of the history of higher education in Britain and the University of Oxford was a general model (1852-1996) of the importance of the university and the advantages of the higher education system in Britain. In 1852, the beginning of the promulgation of reform laws of the University of Oxford, and then began many laws to develop education in Britain, 1996, which introduced comprehensive quality reforms to educational institutions, which aims to develop education in a high and distinctive manner. The study tried to find out the difficulties and obstacles encountered during Oxford University during the period of study, although it was studied by many scientists and personalities in different disciplines that emerged in the world and won many awards internationally, as Oxford University is not only university, but Is an integrated institution providing all the qualifications of study and other life activities.